Are strategic orientations and managerial characteristics drivers of performance in the US wine industry?. Issue 1 (12th March 2018) - Gilinsky, Armand; Newton, Sandra; Eyler, Robert
Abstract : Purpose: The purpose of this study is to investigate the impact of strategic orientations and managerial characteristics on the performance of wine businesses in the US wine industry. Also considered is the power of firm size as measured by production and firm age since founding, as moderating variables that could attenuate or heighten their impact. Design/methodology/approach: Data were gathered via an online survey, where 306 representatives of the US wineries responded. Data are analyzed using descriptive statistics, multinomial logistic regression, cross-tabulations and Pearson chi-square (χ 2 ) analysis. Findings: Wine businesses that reported increased sales and profits over the previous three years made significant changes to organizational structure and staffing levels. Wineries that reported flat or decreasing sales and profits were less apt to make changes in organizational structure or staffing levels. Firm age was found to mediate performance in terms of incremental sales and profit growth; firm size was found to mediate only incremental profit growth. Practical implications: Developing skills in marketing, strategic planning and entrepreneurial thinking to build a defensible industry position and to create the staffing and structure to support that position appear to be of great importance to wine businesses. Originality/value: This study develops and tests a model investigating how firm size and age impact strategic orientations and managerial characteristics on the performance of the US wine businesses. This study investigates which strategic orientations and managerial characteristics wine businesses need to be successful in the future.